(3JNQjL CMGOjK GdHROhis - (3bGSe Hf bWdhHZG, Rjf GdOjf, CHh GdYOd GdShOhfj GdLeGdj,J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO gPG JNQjL eG PcQ ai cJGH GdHROhi ai CUhd Gdabg ef GdCMGOjK hGdBKGQ s
(3BNQgG (B:s
(3hbO Qhi GdHNGQi hCHh OGhO bUI NHjH , hde jPcQ GdEcQGg Ydi GdcaQ hGddg CYde Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B319 - (3U(B380s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG ebGHdIhJUMjM cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs